1995
DOI: 10.1007/bf00177405
|View full text |Cite
|
Sign up to set email alerts
|

Caste allocation in litter Pheidole: lessons from plant defense theory

Abstract: Springer-Verlag 1995 M i c h a e l K a s p a r i • M a r g a r e t M . B y r n e A b s t r a c t The allocation to growth, defense and reproduction varies in social insects within a species' life cycle and between species. A life cycle model (Oster and Wilson 1978) generally failed to predict caste allocation in small litter-nesting colonies of NeotropicalPheidole. Two of its assumptions were often invalid:food was unlikely to be limiting in four of five populations, and sexual biomass production accelerated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Whether this is high enough to prevent colonies from reaching their limiting size is unclear. Yet, a non-saturating increase in colony productivity with colony size has also been reported for many ants and other hymenopterans (Kaspari & Byrne, 1995;Kaspari, 1996;Billick, 2001;Bouwma et al, 2006;McGlynn, 2006;Smith et al, 2007). Taken together, these results suggest that, under natural conditions, colony growth is less constrained than usually assumed.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Whether this is high enough to prevent colonies from reaching their limiting size is unclear. Yet, a non-saturating increase in colony productivity with colony size has also been reported for many ants and other hymenopterans (Kaspari & Byrne, 1995;Kaspari, 1996;Billick, 2001;Bouwma et al, 2006;McGlynn, 2006;Smith et al, 2007). Taken together, these results suggest that, under natural conditions, colony growth is less constrained than usually assumed.…”
Section: Discussionsupporting
confidence: 66%
“…This result also contrasts with the suggestion of a colony size threshold for reproduction in termites, albeit this is based on very few species (Lepage & Darlington, 2000). In the better studied Hymenoptera, the uncoupling between reproduction and colony size seems to be at least as common as size-dependent reproduction within species (Kaspari & Byrne, 1995;Beekman et al, 1998;Cole, 2009). Importantly, we found that alate number was independent of worker number even when considering breeding colonies only, so that variation in breeding status among colonies cannot account for this result.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…have multiple queens). Polygyny is in turn correlated with dependent colony founding and ecological dominance (Boulay et al, 2014 ) and hypothesised to be associated with morphological differentiation in the worker caste (worker polymorphism; Bourke, 1999 ; Anderson & McShea, 2001 ), with fast‐growing colonies investing more in soldier castes (Kaspari & Byrne, 1995 ). Furthermore, polygyny may facilitate social parasitism because colonies accept returning young queens (Buschinger, 1990 ).…”
Section: Key Ecological Strategies Of Ants That Parallel Those Of Plantsmentioning
confidence: 99%
“…According to the superorganism concept, the functionally sterile workers can be compared to somatic tissue and the reproductive queens to the germ line (Oster and Wilson, 1978;Moritz and Fuchs, 1998). Like multicellular organisms, social insect colonies display trade-offs in resource allocation between growth, defense, and reproduction (Sudd and Franks, 1987;Bourke and Franks, 1995;Kaspari and Byrne, 1995). Colony mortality and resource allocation trade-offs are fundamentally different between colonies with one queen (monogynous), in which colony survival is determined by queen survival (Franks et al, 1990a;Pamilo, 1991), and polygynous colonies (with several queens) in which colonies are potentially immortal through serial polygyny (Seppa, 1994).…”
Section: Introductionmentioning
confidence: 99%